2011
DOI: 10.1210/me.2011-0065
|View full text |Cite
|
Sign up to set email alerts
|

TSH Compensates Thyroid-Specific IGF-I Receptor Knockout and Causes Papillary Thyroid Hyperplasia

Abstract: Although TSH stimulates all aspects of thyroid physiology IGF-I signaling through a tyrosine kinase-containing transmembrane receptor exhibits a permissive impact on TSH action. To better understand the importance of the IGF-I receptor in the thyroid in vivo, we inactivated the Igf1r with a Tg promoter-driven Cre-lox system in mice. We studied male and female mice with thyroidal wild-type, Igf1r(+/-), and Igf1r(-/-) genotypes. Targeted Igf1r inactivation did transiently reduce thyroid hormone levels and signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 48 publications
3
19
0
1
Order By: Relevance
“…Both mutant mouse lines were fertile and showed apparently normal phenotypes, although we noticed significant overweig in Nkx2-1-Cre; Igf1r fl/fl mice after puberty when compared with Igf1r fl/fl normal littermates (data not shown), condition that could be due to the lack of Igf1r in thyroid cells as a consequence of Cre expression in these cells driven by the Nkx2-1 promoter, as previously reported [40, 43]. Accordingly, mice with a homozygous thyroidal null mutation in the Igf1r locus also showed increased body weight [44]. A PCR-based analysis of genomic DNA, obtained from a variety of tissues to determine the Cre-mediated deletion in the Igf1r gene (S1 Fig, panels D-G), demonstrated that it specifically occurs in the adult lungs of both double transgenic mutants, but with much higher efficiency in Nkx2-1-Cre; Igf1r fl/fl (Fig 2A) than in Scgb1a1-Cre; Igf1r fl/fl mice (S1 Fig, panels F-G).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Both mutant mouse lines were fertile and showed apparently normal phenotypes, although we noticed significant overweig in Nkx2-1-Cre; Igf1r fl/fl mice after puberty when compared with Igf1r fl/fl normal littermates (data not shown), condition that could be due to the lack of Igf1r in thyroid cells as a consequence of Cre expression in these cells driven by the Nkx2-1 promoter, as previously reported [40, 43]. Accordingly, mice with a homozygous thyroidal null mutation in the Igf1r locus also showed increased body weight [44]. A PCR-based analysis of genomic DNA, obtained from a variety of tissues to determine the Cre-mediated deletion in the Igf1r gene (S1 Fig, panels D-G), demonstrated that it specifically occurs in the adult lungs of both double transgenic mutants, but with much higher efficiency in Nkx2-1-Cre; Igf1r fl/fl (Fig 2A) than in Scgb1a1-Cre; Igf1r fl/fl mice (S1 Fig, panels F-G).…”
Section: Resultssupporting
confidence: 65%
“…Accordingly, lack of Igf1 and Igf1r was reported to promote cell proliferation and/or to alter epithelial differentiation not only in the lung [25, 26, 28, 29, 31], but also in the prostate, thyroid gland, liver and nervous system[31, 44, 72, 73]. Furthermore, limited activity of Igf1r accelerates tumorigenesis and promotes more aggressive phenotypes in prostate and breast cancer in mice [72, 74].…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear why different IGF-Idependency of IRS-2 translocation was shown in subcellular fractionation of HEK293 cells and FRTL-5 cells (Figs 4d and 5d). Thyroid epithelial cells synergistically proliferate in response to IGF-I and TSH in vitro [43][44][45] , which is thought to be important for thyroid morphogenesis and thyroid hormone homeostasis 46 . We previously reported that TSH or other cAMP-generating reagents enhance IGF-I-induced cell proliferation in thyroid FRTL-5 cells 44 .…”
Section: Discussionmentioning
confidence: 99%
“…In dog and human thyroid primary cultures, the presence of insulin receptors strictly depends on TSH and also mediates a comitogenic action of physiologic insulin concentrations, suggesting that thyroid might be a more specific target of insulin than generally considered. 22 Whether that could explain the observation that elevated TSH compensates thyroid-specific IGF-1 receptor knockout in mice 23 remains to be explored.…”
Section: K E Y P O I N T Smentioning
confidence: 99%